Crystal structure of a fluorescent C‐shaped molecule containing closely stacked bithiophene‐substituted quinoxaline rings. Issue 3 (13th February 2017) - Wickham, Laura M.; Tanski, Joseph M.; Nadeau, Jocelyn M.
Abstract : The structural characterization of a C‐shaped molecule with closely stacked bithiophene‐substituted quinoxaline rings revealed π‐stacking interactions between the quinoxaline rings that are responsible for some of its photophysical properties. Abstract : Molecules with well‐defined structures that feature closely stacked aromatic rings are important for understanding π–π interactions. A previously reported C‐shaped molecule with bithiophene‐substituted quinoxaline rings suspended from an aliphatic bridge that holds the aromatic rings in close proximity exists as a pair of syn and anti diastereomers. The anti isomer, namely (1α, 2β, 4β, 5α, 16α, 17β, 19β, 20α)‐1, 5, 16, 20‐tetrachloro‐31, 31, 32, 32‐tetramethoxy‐11, 26‐bis[5‐(thiophen‐2‐yl)thiophen‐2‐yl]‐7, 14, 22, 29‐tetraazanonacyclo[18.10.1.1 5, 16 .0 2, 19 .0 4, 17 .0 6, 15 .0 8, 13 .0 21, 30 .0 23, 28 ]dotriaconta‐6(15), 7, 9, 11, 13, 21(30), 22, 24, 26, 28‐decaene chloroform monosolvate, C48 H36 Cl4 N4 O4 S4 ·CHCl3, whose X‐ray structure is described herein, has cofacial quinoxaline rings with bithiophene rings attached on opposite sides. The molecular structure is approximately C‐shaped and consists of an aliphatic spacer with a boat‐shaped cyclohexane ring in the middle. The centroid‐to‐centroid distance between the quinoxaline rings is 3.950 (1) Å, with ring‐offset distances of 0.354 (3) and 0.816 (2) Å. The pendant bithiophene rings are oriented parallel to one another, which results from the thiophene rings connected to the quinoxaline rings being oriented such that their S atoms are rotated inward toward one another, but are not overlapped. Intermolecular packing is largely governed by van der Waals forces and a few weak C—H… X ( X = N or O) interactions.